First Aid Training Model for Physical Education Teachers - Lubis, Ade Evriansyah; Nugroho, Agung (Prodi PGSD Penjas FPOK UPI, 2021)
The student safety during Physical Education learning process is an important aspect that becomes a responsibility of every Physical Education teacher. Therefore, every Physical Education Teacher must have special supporting skills for handling and giving first aid for various types of physical problems and accidents experienced by students. For this reason, it is necessary to conduct a study aimed at developing a first aid training model for Physical Education teachers. The method used in this study was Research Development model, using the ADDIE approach (Analysis, Design, Development, Implementation, Evaluation). The population of this study were Physical Education Teachers in Medan Deli District, Medan Municipality, North Sumatra Province, in 2019. The respondents included 99 Physical Education teachers selected through total sampling technique. The data collection techniques used in this study were interviews and online questionnaire distribution. The data analysis technique used was descriptive analysis technique. The research results show the total score mean (X) validation of 2 First Aid Training Experts was 71.00 and the total score mean (X) validation of 2 Physical Education Experts was 73.00. Based on the quantitative data obtained from the mean score calculation (X), the qualitative value was obtained (51.00 â‰¤ X â‰¤ 75.00). It concludes that the First Aid Training Model for Physical Education Teachers is feasible to be used as a support for Physical Education learning in schools.